Healthcare-associated infections point prevalence survey and antimicrobials use in acute care hospitals (PPS 2016-2017) and long-term care facilities (HALT-3): a comprehensive report of the first experience in Molise Region, Central Italy, and targeted intervention strategies - Giancarlo Ripabelli; Angelo Salzo; Andrea Mariano; Michela L. Sammarco; Manuela Tamburro (Elsevier, 2019)
Background: Healthcare associated infections (HAIs) are a major public health concern both in acute hospitals and long-term care facilities (LTCFs), considering the clinical presentations and related costs. The study describes the first regional experience on HAIs and antimicrobials consumption obtained through point prevalence survey (PPS) 2016-2017 in the "Antonio Cardarelli" acute hospital, and in the LTCF of Larino municipality (Healthcare-associated infections and Antimicrobial use in European Long-Term care facilities, HALT-3) of Molise Region, Central Italy, both coordinated by the European Center for Disease Control (ECDC). Methods: PPS was carried out during 24-26 November 2016, while HALT-3 on 29 June 2017. Standardized protocols and software provided by ECDC were used to collect facilities information, patients/residents, HAIs and antibiotic consumption data. Results: An active HAI was found in 16 (7.1%) of 224 admitted patients in the acute hospital, and 50% occurred in a clinical specialty ward. Bundles, checklist for HAIs prevention and antimicrobial stewardship were lacking. Among 29 LTCF residents the HAIs prevalence was 3.4%. Surveillance programs for HAIs and antimicrobial stewardship strategy were not available. Conclusion: The overall results identified the need and types of interventions to be implemented in both settings, either at organizational or individual level, to improve antibiotic prescription practice and limit risk factors involved in potentially preventable infections. Keywords: Healthcare-associated infections, Antibiotic use, Surveillance, Point prevalence survey, Italy